Peace and conflict studies - Barash, David P.; Webel, Charles P. (Sage Publications, 2014)
This thoroughly revised Third Edition of Peace and Conflict Studies, by David P. Barash and Charles P. Webel, sets the gold standard as an accessible introduction and comprehensive exploration of this vital subject. The authors share their vast knowledge and analysis of 21st-century world events-including new coverage on timely topics such as the scope and history of peace and conflict studies, the nature of violence and nonviolence, cutting-edge military technologies, the rise of the "BRIC" countries, and the US and Global Peace Indexes. With an encyclopedic scope, this introductory book chronicles a plethora of important global topics from pre-history to the present